Analysis of accidental time work parameters in the organizational & technological model for erection of the frame-monolithic building - Tytok, V.; Yemelianova, O. (Ways to Improve Construction Efficiency, 2019)
The article deals with a method of simulation modeling, that takes into account the peculiarities of its use in the conditions of a frame-monolithic building erection. The method of simulation modeling is developed. The essence of this method is in usage a Monte Carlo method for performing one work and construction of the entire object for a two-factor beta distribution. The empirical regularities that characterize the duration of individual works anderection stages of a frame-monolithic building are obtained.